DEVELOPMENT PERFORMANCES OF AGRICULTURE IN THE DANUBE REGION COUNTRIES - Gajić, Milivoj; Matkovski, Bojan; Zekić, Stanislav; Đokić, Danilo (Economics of Agriculture, 2015)
In the recent decades, the Danube Region countries profle their policies towards a more effcient way of exploiting the natural resources of the Danube basin. The Danube can contribute to a better integration of the countries, enhancing economic opportunities through diversifcation and promotion of rural development. The trend analysis in the agricultural sector of the Danube Region countries refers to the frst decade of this century, and it begins with the determination of the agricultural importance in the overall economy. The development performances of agriculture in the Danube Region countries are considered according to the production and export performances of this economic sector, using a comparative approach. The agricultural production growth, level and growth of the partial agricultural productivities - labour and land, as well as the value of exports in relation to engaged labour and agricultural land, are analysed in such a context.